Sub‐Nanometer Nanobelts Based on Titanium Dioxide/Zirconium Dioxide–Polyoxometalate Heterostructures. Issue 23 (27th April 2021) - Zhang, Simin; Liu, Nan; Wang, Hongwei; Lu, Qichen; Shi, Wenxiong; Wang, Xun
Abstract: In addition to offering conformational flexibility, sub‐nanometer nanobelts (SNBs) also outperform many larger nanobelts with large size owing to their ultrathin morphologies. However, to date, only a few monocomponent SNBs have been synthesized. This study presents a facile method for synthesizing ZrO2 –PMoO (PMZ) SNBs and TiO2 –PMoO (PMT) SNBs with heterostructures. The SNBs comprise ZrO2 /TiO2 and polyoxometalate (POM) nanoclusters, which are formed via the aggregation and subsequent transformation of nanoclusters. Significantly, these SNBs demonstrate high catalytic activity and stability in oxidative desulfurization reactions at room temperature. The impressive catalytic performance of the SNBs is aided by the POM nanoclusters, which not only coassemble with ZrO2 /TiO2 nuclei to form building blocks of PMZ SNBs/PMT SNBs but also serve as catalytic centers. The catalytic performance is further enhanced by the ZrO2 /TiO2 in the SNBs. Moreover, the proposed synthesis method can be utilized to produce other SNBs. Thus, this method provides valuable insights into the strong performance properties of SNBs created by combining metal oxides and POM nanoclusters into SNBs, which have great potential as redox catalysts. Abstract : ZrO2 –PMoO (PMZ) sub‐nanobelts (SNBs) and TiO2 –PMoO (PMT) SNBs are constructed through a nanoclusters gathering–transforming process, composed of ZrO2 /TiO2 and polyoxometalate (POM) nanoclusters, showing high catalytic activity and stability in the oxidative desulfurization reaction at room temperature. The POM nanoclusters not only facilitate the formation of SNBs, but also perform as catalytic centers.